2023
DOI: 10.1002/advs.202304453
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Pharmacokinetics Reveal Impact of Lipid Composition on Microbubble and Nanoprogeny Shell Fate

Maneesha A. Rajora,
Alexander Dhaliwal,
Mark Zheng
et al.

Abstract: Microbubble‐enabled focused ultrasound (MB‐FUS) has revolutionized nano and molecular drug delivery capabilities. Yet, the absence of longitudinal, systematic, quantitative studies of microbubble shell pharmacokinetics hinders progress within the MB‐FUS field. Microbubble radiolabeling challenges contribute to this void. This barrier is overcome by developing a one‐pot, purification‐free copper chelation protocol able to stably radiolabel diverse porphyrin‐lipid‐containing Definity® analogues (pDefs) with >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 130 publications
(186 reference statements)
1
6
0
Order By: Relevance
“…The activation of the C3 pathway triggers the cleavage of C3 into C3b and C3a, initiating the phagocytic process and mediating inflammation or immune responses . Also, it has been reported that the presence of anti-PEG antibodies reduces the half-life of PEGylated drugs by 2–10-fold and increases hepatic and spleen uptake by 2–5 and 1–2-fold, respectively. , This observation corroborates our findings, which predict enhanced MB retention in C 2 , likely the lungs, spleen, and liver, ,, which may be mediated by the complement activation. Thus, the secondary mechanism of MB clearance in C 2 can be attributed to phagocytosis by resident macrophages within the clearance organs.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The activation of the C3 pathway triggers the cleavage of C3 into C3b and C3a, initiating the phagocytic process and mediating inflammation or immune responses . Also, it has been reported that the presence of anti-PEG antibodies reduces the half-life of PEGylated drugs by 2–10-fold and increases hepatic and spleen uptake by 2–5 and 1–2-fold, respectively. , This observation corroborates our findings, which predict enhanced MB retention in C 2 , likely the lungs, spleen, and liver, ,, which may be mediated by the complement activation. Thus, the secondary mechanism of MB clearance in C 2 can be attributed to phagocytosis by resident macrophages within the clearance organs.…”
Section: Resultssupporting
confidence: 91%
“…Overall, increasing the MVD to 40 μL/kg extended circulation time from ∼20 to ∼30 min. MB clearance primarily involved dissolution and elimination by the lungs in C 1 , while MB retention is expected to occur in the liver, lungs, and spleen in C 2 . ,,, Both the 10 and 5 mol % configurations displayed slightly accelerated biexponential decay when compared to the 2 mol % configuration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations